(untitled) (Web of Teachers: Inderscience Research, 2025)
This article explores innovative and digitally-integrated vocational training methods aimed at enhancing student competencies in clothing design and modeling. With the rapid advancement of digital technologies, traditional teaching methods in fashion education face challenges in meeting modern industry demands. The study proposes a methodological framework that incorporates 3D modeling software, computer-aided design (CAD), and creative problem-solving techniques to improve both theoretical knowledge and practical skills. The implementation of these approaches prepares students for the evolving labor market, fostering their professional growth and adaptability. The findings highlight the positive impact of integrating digital tools into vocational training, recommending their broader application in fashion education curricula.